Conscience, Law, and Politics - Hannon, Patrick (Religions, 2022)
Of the many questions on which our title invites reflection, one in particular has again achieved prominence in the United States: how is a politician who is Roman Catholic expected to vote when a measure purports to legalise what church teaching says is morally wrong? The debate has become increasingly acrimonious, to the point where senior prelates are among those who contend that President Biden and Speaker of the House Pelosi are unfit to receive Holy Communion since they subscribe to the ‘pro-choice’ position of the Democratic Party. The core question has become politicised, its public discussion poisoned by association with toxic elements of the so-called ‘culture wars’, at an impasse that is impairing effective leadership in the US Catholic Church, and an effective Catholic contribution to the common good of American society. I shall argue that this is as unnecessary as it is regrettable, and that a way through the impasse is to be found in mainline Catholic thinking about morality, law, and politics.